Design of parallel transmission pulses for simultaneous multislice with explicit control for peak power and local specific absorption rate. Issue 5 (17th June 2014) - Guérin, Bastien; Setsompop, Kawin; Ye, Huihui; Poser, Benedikt A.; Stenger, Andrew V.; Wald, Lawrence L.
Abstract : Purpose: To design parallel transmit (pTx) simultaneous multislice (SMS) spokes pulses with explicit control for peak power and local and global specific absorption rate (SAR). Methods: We design SMS pTx least‐squares and magnitude least squares spokes pulses while constraining local SAR using the virtual observation points (VOPs) compression of SAR matrices. We evaluate our approach in simulations of a head (7T) and a body (3T) coil with eight channels arranged in two z‐rows. Results: For many of our simulations, control of average power by Tikhonov regularization of the SMS pTx spokes pulse design yielded pulses that violated hardware and SAR safety limits. On the other hand, control of peak power alone yielded pulses that violated local SAR limits. Pulses optimized with control of both local SAR and peak power satisfied all constraints and therefore had the best excitation performance under limited power and SAR constraints. These results extend our previous results for single slice pTx excitations but are more pronounced because of the large power demands and SAR of SMS pulses. Conclusions: Explicit control of local SAR and peak power is required to generate optimal SMS pTx excitations satisfying both the system's hardware limits and regulatory safety limits. Magn Reson Med 73:1946–1953, 2015. © 2014 Wiley Periodicals, Inc.